2022
DOI: 10.3390/diagnostics12081918
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Tumor Mutation Burden and Immune Infiltrates in Hepatocellular Carcinoma

Abstract: Tumor mutation burdens (TMBs) act as an indicator of immunotherapeutic responsiveness in various tumors. However, the relationship between TMBs and immune cell infiltrates in hepatocellular carcinoma (HCC) is still obscure. The present study aimed to explore the potential diagnostic markers of TMBs for HCC and analyze the role of immune cell infiltration in this pathology. We used OA datasets from The Cancer Genome Atlas database. First, the “maftools” package was used to screen the highest mutation frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A recently published study identified the NCBP2 gene among the highly mutated genes in high-TMB HCC patients. This gene is involved in the regulation of proliferation, metastasis, and apoptosis, and has been proposed as a novel biomarker of carcinogenesis and cancer progression [ 150 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…A recently published study identified the NCBP2 gene among the highly mutated genes in high-TMB HCC patients. This gene is involved in the regulation of proliferation, metastasis, and apoptosis, and has been proposed as a novel biomarker of carcinogenesis and cancer progression [ 150 ].…”
Section: Combination Of Tmb and Other Specific Genetic Biomarkersmentioning
confidence: 99%
“…The clusterProfiler package (version 4.2.2) 38 was used to implement the GO and the Kyoto Encyclopedia of KEGG enrichment of DE-ALI-OSRGs, and the enrichment results were visualized using GOplot (version 1.0.2) 39 and enrichplot packages (version 1.10.2) 40 .…”
Section: Methodsmentioning
confidence: 99%
“…We conducted Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses to identify the biological role of the cellular senescence‐related differentially expressed genes (DEGs) using “Clusterprofiler,” “http://org.hs.eg.db,” “ggplot2,” and “enrichplot” R packages between different risk groups 21 …”
Section: Methodsmentioning
confidence: 99%